Diarylethenes in Optically Switchable Organic Light‐Emitting Diodes: Direct Investigation of the Reversible Charge Carrier Trapping Process. Issue 2 (2nd November 2021) - Cotella, Giovanni F.; Bonasera, Aurelio; Carnicella, Giuseppe; Minotto, Alessandro; Hecht, Stefan; Cacialli, Franco
Abstract: The design, fabrication, and characterization of optically switchable organic light‐emitting diodes (OSOLEDs) based on the combination of the commercially available light‐emitting polymer poly(9, 9′‐dioctylfluorene‐ alt ‐benzothiadiazole), F8BT, doped with a diarylethene derivative is reported. The photochromic activity of the dopant in the solid state has been investigated both via UV/vis absorption and photoluminescence spectroscopy, whereas the morphology of different blends is investigated via atomic force microscopy. OSOLEDs embedding dopant loadings of 1, 5, and 10 wt% exhibit optical responsivity with a maximum reversible optical threshold voltage shift of 4 V. The best performing devices containing 5 wt% dopant show a maximum current density and luminance ON/OFF ratio of ≈20 and ≈90, respectively. For the first time, the impact of the diarylethene isomerization on hole and electron transport has been decoupled and directly investigated, via the design, fabrication, and characterization of single‐carrier switchable devices based on the same blends. Not only do these results confirm the photo‐responsive trapping activity of the diarylethenes on both charge carriers, but they also demonstrate its asymmetry, with a predominant effect on electron transport that is over 3.4 times larger as compared to hole transport. Abstract : Optically switchable organic light‐emitting diodes have been achieved by doping a diarylethene (DAE) derivative into the light‐emitting polymer poly(9, 9′‐dioctylfluorene‐ alt ‐benzothiadiazole), F8BT. Switching is based on the reversible charge carrier trapping by the DAE.